2019
DOI: 10.3390/su11082205
|View full text |Cite
|
Sign up to set email alerts
|

Walkability Assessment in a Rapidly Urbanizing City and Its Relationship with Residential Estate Value

Abstract: Walkability has increasingly been recognized as an important factor for sustainable urban development that, however, has seldom been investigated in rapid urbanizing cities, especially in the Asian context. This paper assessed walkability in Futian District in the central area of Shenzhen, which has undergone very rapid urbanization within a short period of time. Walkability was assessed for 2013 and 2018 using a walkability index adapted from Walk Score. It was compared with housing prices of 215 randomly sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Many studies have shown that the housing price and level of walkability have a positive correlation [19,20,22]. Meanwhile, a study by Zhang et al showed that the housing price was negatively correlated with the level of walkability in the Futian district in Shenzhen, China [25]. Our task here was to analyze these aspects as they relate to Seoul, Korea.…”
Section: Overall Descriptive Statistics and Spatial Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the housing price and level of walkability have a positive correlation [19,20,22]. Meanwhile, a study by Zhang et al showed that the housing price was negatively correlated with the level of walkability in the Futian district in Shenzhen, China [25]. Our task here was to analyze these aspects as they relate to Seoul, Korea.…”
Section: Overall Descriptive Statistics and Spatial Patternsmentioning
confidence: 99%
“…Reyer et al tried to develop the walk score and investigate its association with active transportation in Stuttgart, Germany [24]. Zhang et al also calculated the walkability level and defined its relationship with residential estate value in Futian District, China [25]. In particular, Zhang and colleagues' study found a negative association between walkability and housing prices in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2019) used a grid point with an interval of 150 m to measure the walkability of the Futian district in China. This is because a 150 m interval was utilized in the original Walk Score calculation method [46]. This study used a spatial unit that was equal to or smaller than 400 m, taking into account the previously used walking distance.…”
Section: Study Areamentioning
confidence: 99%
“…Location and price are often considered to be the two most important factors when looking at real estate; the more walkable an area is the more attractive it is perceived to be. Therefore, neighborhoods with a greater perceived quantity of socioeconomic amenities have improved market values [117]; however, seldom is the quality of those socioeconomic amenities or factors of environmental well-being considered. Home prices and assaults were found negatively associated.…”
Section: Importance Of Relationshipsmentioning
confidence: 99%